A Comparative Analysis of Critical Thinking in Western And Islamic Education: Implications for Contemporary Islamic Pedagogy - Rabiatul Adawiah; Halimatus Sakdiah (SYAMIL: Journal of Islamic Education, 2025)
Critical thinking is an important skill in education, but its conceptualization varies across Western and Islamic paradigms. This study aims to compare the concepts, criteria, and objectives of critical thinking in Western and Islamic education. The research method used is a qualitative literature study by examining primary and secondary sources from Western and Islamic studies, and analyzing them systematically thematic. The main findings reveal that Islamic critical thinking "tafakkur" and "ulul albab” integrating reflection “rational-religious (al-Diny al-Aqlany)” because in it there is tadabbur and tadzakkur, while Western critical thinking emphasizes “rationality-progressivism”. Critical thinking aims to enable a person to understand themselves, their environment, and their world, so they can make good decisions, solve problems, and produce something new. Meanwhile, in Islam, purpose tafakkur and ulul albab is "ma’rifat”. Ma’rifat is the knowledge of knowing Allah, knowing oneself, knowing the world, and knowing the afterlife. In Islam critical thinking is not only sharp mind, but also sharp awareness of the heart so that it becomes wiser. Although critical thinking from a Western and Islamic perspective tends to differ in concepts, criteria, and objectives, integration between the two is very important. Synergy between Western and Islamic education is needed to design a holistic curriculum that is responsive to the challenges of contemporary Islamic pedagogy.